Thermal response of Josephson junction arrays on silicon nitride membranes - Zarate, J.J. (2009)
Fil: Zarate, J.J. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina